A cost effective trade-off based renewable power augmented energy efficient load model for manufacturing industries for demand side management. Issue 1 (31st December 2016) - Parida, Adikanda; Choudhury, Shibabrata; Chatterjee, Saibal; Chatterjee, Debashis
Abstract: Efficient utilization of electrical energy plays a significant role for sustainable development of the industries. Moreover, effective implementation of energy efficiency technology in the industrial infrastructure and production chain is a part of smart grid mission. However, the cost effectiveness of the project is always a constraint for adoption and implementation. In this paper, for demand side management, an appropriate rule based strategy has been proposed which improves the energy efficiency of a production unit in a cost effective manner. Also, an attempt has been made to develop a fair trade-off based captive renewable power augmentation scheme which will further enhance the cost effectiveness of the presented energy efficiency model for the plant. Moreover, this approach can significantly reduce the maximum demand of the plant which will unburden the power utility. The developed model has been applied in a cement-asbestos industry considered for case-study which produces satisfactory results. The proposed model can be suitably customized for other type of production industries. The trade-off mechanism has been validated using HOMER Pro-3.2 software.